INVESTIGATION OF A NEW TRANSITION CURVE - Tasci, Levent; Kuloglu, Necati (Vilnius Gediminas Tech Univ, 2011)
This paper describes derivation of the curvature change for the transition curve in a 2(nd) degree increasing concave formulation. The investigation of the usability of the developed transition curve in new designs and rehabilitation of existing roads are also included in this study. New transition curves are compared with the most used transition curves (clothoid, sinusoidal and bloss) in highways, and it has been targeted to indicate whether it is the most economic and comfortable one or not.
Naüjös pereinamösiös kreiv?s tyrimas
Keywords: highway; transition curve; curvature; superelevation; clothoid; bloss; sinusoidal